Influence of dietary nitrate supplementation on high-intensity intermittent running performance at different doses of normobaric hypoxia in endurance-trained males - Robinson, G. P.; Killer, S. C.; Stoyanov, Z.; Stephens, H.; Read, L.; James, L. J.; Bailey, S. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
This study investigated whether supplementation with nitrate-rich beetroot juice (BR) can improve high-intensity intermittent running performance in trained males in normoxia and different doses of normobaric hypoxia. Eight endurance-trained males (VO2peak, 62 ± 6 ml·kg-1·min-1) completed repeated 90 s intervals at 110% of peak treadmill velocity, from an initial step incremental test, interspersed by 60 s of passive recovery until exhaustion (Tlim). Participants completed the first three experimental trials during days 3, 5, and 7 of BR or nitrate-depleted beetroot juice (PLA) supplementation and completed the remaining experimental visits on the alternative supplement following at least 7 days of washout. The fraction of inspired oxygen during visits 1-3 was either 0.209, 0.182, or 0.157, equivalent to an altitude of 0, 1,200, and 2,400 m, respectively, and this order was replicated on visits 4-6. Arterial oxygen saturation declined dose dependently as fraction of inspired oxygen was lowered (p < .05). Plasma nitrite concentration was higher pre- and postexercise after BR compared with PLA supplementation (p < .05). There was no difference in Tlim between PLA and BR at 0 m (445 [324, 508] and 410 [368, 548] s); 1,200 m (341 [270, 390] and 332 [314, 356] s); or 2,400 m (233 [177, 373] and 251 [221, 323] s) (median and [interquartile range]; p > .05). The findings from this study suggest that short-term BR supplementation does not improve high-intensity intermittent running performance in endurance-trained males in normoxia or at doses of normobaric hypoxia that correspond to altitudes at which athletes typically train while on altitude training camps.